2010
DOI: 10.1016/j.clinph.2010.02.166
|View full text |Cite
|
Sign up to set email alerts
|

Stretch sensitive reflexes as an adaptive mechanism for maintaining limb stability

Abstract: The often studied stretch reflex is fundamental to the involuntary control of posture and movement. Nevertheless, there remains controversy regarding its functional role. Many studies have demonstrated that stretch reflexes can be modulated in a task appropriate manner. This review focuses on modulation of the long latency stretch reflex, thought to be mediated, at least in part, by supraspinal pathways. For example, this component of the stretch reflex increases in magnitude during interactions with compliant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 90 publications
4
79
1
2
Order By: Relevance
“…In Fast, total perturbation time was ϳ600 ms, so central processing may be as crucial as efficient sensory feedback. It has been suggested that group II afferent fibers and supraspinal pathways contribute to MLR and LLR responses, respectively (Grey et al 2001;Schieppati and Nardone 1997;Shemmell et al 2010). In the present study, Elderly showed larger SOL MLR and LLR responses during posterior perturbations.…”
Section: Discussionsupporting
confidence: 61%
“…In Fast, total perturbation time was ϳ600 ms, so central processing may be as crucial as efficient sensory feedback. It has been suggested that group II afferent fibers and supraspinal pathways contribute to MLR and LLR responses, respectively (Grey et al 2001;Schieppati and Nardone 1997;Shemmell et al 2010). In the present study, Elderly showed larger SOL MLR and LLR responses during posterior perturbations.…”
Section: Discussionsupporting
confidence: 61%
“…Our results, however, are in contrast with those of Madhavan and Shields (2011), who reported higher amplitude of long-latency muscle responses to unexpected perturbations in patients with ACLR compared to healthy individuals during a dynamic single-leg weight-bearing task. The differences between Madhavan and Shields (2011) and the results of the present study might be attributed to the task being performed, since long-latency responses may be modulated in a manner appropriate to meet the motor demands and give protection to forthcoming perturbations (Dietz et al 1994;Shemmell et al 2010;Pruszynski et al 2011). The weight-bearing task being performed in Madhavan and Shields (2011) is a closed kinetic chain movement, in which activation of the knee extensor muscles causes lower anterior shear 15 forces on the tibia and lower strain on the ACL than during open kinetic chain movements (Lutz et al 1993) that are similar to the semi-reclined task in this study.…”
Section: Compensatory Postural Responses To Unpredictable Perturbationsmentioning
confidence: 74%
“…This position is supported by many demonstrations that muscular activity 50 -100 ms after a mechanical perturbation (i.e., the long-latency stretch response) shows a range of modulation that reflects voluntary motor control (for review see Pruszynski and Scott 2012;Shemmell et al 2010). Such modulation of the long-latency stretch response reflects sensitivity to task demands (Dietz et al 1994;Doemges andRack 1992a, 1992b;Hager-Ross et al 1996;Marsden et al 1981;Nashed et al 2012), movement decision-making processes (Nashed et al 2014;Selen et al 2012;Yang et al 2011), routing of sensory information across different muscles (Cole et al 1984;Dimitriou et al 2012;Marsden et al 1981;Mutha and Sainburg 2009;Ohki and Johansson 1999;Omrani et al 2013), as well as knowledge of the mechanical properties of the arm (Crevecoeur et al 2012;Crevecoeur and Scott 2013;Gielen et al 1988;Koshland et al 1991;Kurtzer et al 2008Kurtzer et al , 2009Kurtzer et al , 2013Kurtzer et al , 2014Pruszynski et al 2011a;Soechting and Lacquaniti 1988) and environment (Ahmadi-Pajouh et al 2012;Akazawa et al 1983;Bedingham and Tatton 1984;Cluff and Scott 2013;Dietz et al 1994;Kimura et al 2006;Krutky et al 2010;Perreault et al 2008;Pruszynski et al 2009;Shemmell et al 2009...…”
mentioning
confidence: 73%
“…This difference between the short-latency and long-latency stretch responses likely reflects differences in the neural circuitry that underlies the muscle activity in these epochs (for reviews see Matthews 1991;Pruszynski 2014;Pruszynski and Scott 2012;Shemmell et al 2010). Briefly, the timing of the short-latency stretch response, appearing on the muscle ϳ25-50 ms after perturbation onset, requires that it engage a spinal circuit mediated by relatively large-diameter afferent fibers (PierrotDesilligny and Burke 2005).…”
Section: Discussionmentioning
confidence: 99%